2013
DOI: 10.1007/s10151-013-1014-y
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative blood transfusion in cancer patients undergoing laparoscopic colorectal resection: risk factors and impact on survival

Abstract: Perioperative blood transfusion is associated with decreased long-term survival in patients undergoing laparoscopic resection for colorectal cancer. However, this association apparently reflects the poorer medical condition of patients requiring surgery and not a causative relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
2
13
0
1
Order By: Relevance
“…There is a marked difference in 30‐day mortality between completed laparoscopic surgery and conversion which can be accounted for by intra‐operative complications necessitating conversion to an open procedure. Perioperative blood transfusion appears to be more frequently required after conversion in this analysis, and there is some evidence that this may increase the risk of recurrence . The inflammatory response provoked by more extensive surgical resection and postoperative complications in conversion patients is also likely to contribute to an adverse outcome.…”
Section: Discussionmentioning
confidence: 84%
“…There is a marked difference in 30‐day mortality between completed laparoscopic surgery and conversion which can be accounted for by intra‐operative complications necessitating conversion to an open procedure. Perioperative blood transfusion appears to be more frequently required after conversion in this analysis, and there is some evidence that this may increase the risk of recurrence . The inflammatory response provoked by more extensive surgical resection and postoperative complications in conversion patients is also likely to contribute to an adverse outcome.…”
Section: Discussionmentioning
confidence: 84%
“…Data on OS were from 24 articles [14, 8, 9, 11, 13, 14, 16, 17, 19, 21, 22, 24, 2830, 3236, 38]. The random-effects model showed that transfusion could decrease OS significantly (HR, 0.33; 95% CI, 0.24 to 0.41; I 2 = 61.9%; P < 0.0001; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, not all reports have come to the same conclusion [9] and considerable controversy persists regarding cause and effect. In this context, relationships between the need for blood transfusions and other confounders that may contribute to increased risk of adverse outcomes may exist [9]. …”
Section: Introductionmentioning
confidence: 99%